Creativity in lockdown: Understanding how music and the arts supported mental health during the COVID-19 pandemic by age group - Chmiel, Anthony; Kiernan, Frederic; Garrido, Sandra; Lensen, Sarah; Hickey, Martha; Davidson, Jane W. (Frontiers in Psychology, 2022)
Recent research has indicated that many people around the world turned to artistic creative activities (ACAs) to support their mental health during COVID-19 lockdowns. However, studies have also shown that the negative psychosocial impacts of the pandemic have disproportionately affected young people, suggesting that the use of ACAs to support mental health in lockdown may have varied across age groups. This study investigated how Australians in four different age groups (18-24, 25-34, 35-54, and 55+) engaged in ACAs to support their mental health during the 2020 pandemic lockdowns. Participants (N = 653) recruited from the general public completed an online survey between May and October 2020, in which they reported which ACAs they had undertaken during the pandemic using an established list. Participants subsequently ranked undertaken ACAs in terms of effectiveness at making them “feel better”, and those who had engaged in musical ACAs also completed the Musical Engagement Questionnaire (MusEQ). Additionally, ratings of anxiety (GAD7) and depression (PHQ9) symptoms were obtained and examined for potential variations across four demographic and lifestyle variables: age, exercise, gender and state/territory of residence. ACA rankings showed that younger participants overwhelmingly rated musical activities as most effective, while, with the exception of singing, those aged 55+ rated non-musical activities as being most effective. These differences were further supported by ratings for all six MusEQ subscales, with responses strongly indicating that the youngest participants (aged 18-24) used music in significantly different ways during the pandemic than participants in all other age groups. Specifically, these youngest participants were more likely to integrate music into daily life, use music for emotion regulation, respond to music in embodied ways, and use music to perform a social identity. In line with prior research, further analyses indicated that symptoms of anxiety and depression were lessened for older participants, as well for those who reported exercising more during the lockdowns. These findings provide insight into how ACAs can support mental health during a pandemic crisis for specific age groups, which may inform future policy directions, and suggestions for how this can be done are provided.